Discharge against medical advice amongst patients admitted into the Paediatric wards of the University of Port Harcourt Teaching Hospital (NIGERIAN JOURNAL OF PAEDIATRICS, 2024)
Abstract Objectives: To identify the characteristics of patients and factors contributing to DAMA in paediatric patients admitted into the University of Port Harcourt Teaching Hospital and to determine ways to reduce its prevalence.Method: This was a retrospective study of children admitted into the paediatric wards of the Hospital. Case files of affected patients over a two year period were reviewed and relevant information obtained and analyzed.Results: There were 150 of 3981 patients admitted over the period giving a prevalence rate of 3.8%. There were 86 (57.3%) males and 64 females (42.7%) with a male: female ratio of 1.3:1. Neonatal sepsis, birth asphyxia and prematurity were the commonest diagnosis in neonates whilst severe malaria, meningitis and bronchopneumonia were the commonest in other children. Most discharges (54%) occurred within the first week of admission. Majority of patients were from low (35.3%) and middle (41.3%) income classes. The commonest reasons for DAMA were lack of funds (26.6%) and no improvement (26.6%), necessitatingneed to seek alternative therapy. The discharge document was signed by the father in 61.3% of cases.Conclusion: Children who were DAMA suffered from common causes of childhood mortality. Lack of funds, no improvement and lack/ low decision making power of mothers were contributory factors. There is need for more universal implementation of the National Health Insurance Scheme; effective communication between medical team and parents and female empowermentto reduce rates of DAMA in our environment.Keywords: Discharge against medical advice, children, paediatric wards.